An Analysis of Lexicons Related to Wura Bongi Monca Dance in Bima - Maria Yuliana Geofany; I Gede Budasi; Dewa Ayu Eka Agustini (Jurnal Pendidikan Bahasa Inggris undiksha, 2022)
Wura Bongi Monca dance is a classic dance from Bima NTB which has its lexicons. This culture is very important, because if the culture is lost, then the lexicon in dance will be lost.Base on those reason this research was designed in the form of descriptive qualitative study which aimed to analyses lexicons and their culture meaning, their word formations, as well as their word classes. The data of the study were in the forms of primary and secondary data. The primary data were obtained using observing and interviewing technique while the secondary ones  were taken from analyzing the relevant documents found in Bima Museum, NTB. The results of this study show that: (a) 23 lexicons were found in the dance and divided into 3 parts: namely, 7 are connected to its dance movements, 12 to its costumes, and 4 to its musical instruments; (b) In term of  its word formations, 2 types were found; compounding (13), and borrowing (3); and (c) In term of the lexicon word category, only 3 word classes were  found: nouns (27), adjectives (9), and verbs (2).